The use of nasal trumpet as a non-invasive treatment method in congenital nasal stenosis - Kemal, Özgür; Atmaca, Sinan; Bel-Çeçen, Ayşe; Düzgün, Berkan; Aygün, Hasibe Canan (The Turkish Journal of Pediatrics, 2017)
Newborns and infants are dependent on nasal respiration and therefore, nasal obstructions may lead to life-threatening outcomes in this age group. Although the most common cause of nasal obstruction in newborns are choanal atresia, soft tissue edema, congenital nasal bone anomalies such as narrowness of the apertura piriformis and midnasal stenosis should be kept in mind. A 5-day-old infant was referred to our clinic with the complaints of respiratory problems. Physical examination revealed nasal bone hypoplasia and saddle nose deformity. In the endoscopic examination, the septum was seen to be deviated in an `S` shape and the nasal passages were almost completely closed. The paranasal CT examination reported significant narrowing of the airway in the central part of the nasal cavity. After application of nasal trumpet to both nasal passages, clinical recovery was determined in the patient and no pathology was determined during the follow-up period.